DIGITALIZATION OF NATURAL SCIENCE MUSEUM HOLDINGS: PROBLEMS AND PROSPECTS (Universal International Scientific Journal, 2026)
This article provides information on the issues of including museum collections andobjects in the electronic catalog of the national museum fund, the advantages of digitization. Inaddition, several proposals are made on the problems and promising plans for digitizing funds.
Keywords: Museum fund; digitization; electronic catalog